The Human Response to the Death of a Loved One - Briana Evans (Journal of Death, 2026)
Everyone knows that death is a part of life, you live, then you die. But no one is ever truly prepared for the grief response that follows the death of a loved one whom you hold a deep, social, and intimate connection with. This paper explores the neurobiological activations and the multifaceted grief response to the loss of a loved one that is deeply connected to the brain’s collaborative abilities with the body. Throughout the paper, we will focus on the limbic brain and the key role it plays while mediating through the emotions, feelings, and decision-making processes as it responds to the external social environment and stimuli experienced, with the primary focus being on grief. The paper will also critically analyze Antonio Damasio’s theory on reason and emotion and how it pertains to the grief response to offer a thorough understanding of the human response to the death of a loved one and its implications for rational decision-making.
Keywords: grief